Effect of MCI-154 on calcium sensitivity of vascular smooth muscle and its mechanism in hemorrhagic shock in rats - Yang, Guang-ming (Zhongguo wei zhong bing ji jiu yi xue = Chinese critical care medicine = Zhongguo weizhongbing jijiuyixue, 2005)
OBJECTIVE: To observe the effects of new calcium sensitizer MCI-154 on calcium sensitivity of vascular smooth muscle following hemorrhagic shock (HS) in rats, and to explore its mechanism